2011
DOI: 10.1186/1475-925x-10-100
|View full text |Cite
|
Sign up to set email alerts
|

Automatic discrimination between safe and unsafe swallowing using a reputation-based classifier

Abstract: BackgroundSwallowing accelerometry has been suggested as a potential non-invasive tool for bedside dysphagia screening. Various vibratory signal features and complementary measurement modalities have been put forth in the literature for the potential discrimination between safe and unsafe swallowing. To date, automatic classification of swallowing accelerometry has exclusively involved a single-axis of vibration although a second axis is known to contain additional information about the nature of the swallow. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…In this study, 9 features in time, information-theoretic, frequency, and time-frequency domains were evaluated. Further, the practicality of these features had already been demonstrated in previous swallowing signal studies [22], [31], [32], [37], [50]. The computational details for each of these features are described in the following subsections.…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…In this study, 9 features in time, information-theoretic, frequency, and time-frequency domains were evaluated. Further, the practicality of these features had already been demonstrated in previous swallowing signal studies [22], [31], [32], [37], [50]. The computational details for each of these features are described in the following subsections.…”
Section: Methodsmentioning
confidence: 92%
“…On the other hand, some studies have extracted advanced features in time, frequency, and time-frequency domains from swallow vibrations [26], [31]–[34]. The results from past studies have shown the validity of the swallowing accelerometry method’s use of one or two directions of anterior-posterior (A-P) and superior-inferior (S-I), representing the forward and upward movements of hyolaryngeal structures during swallowing, in swallow classification and capturing swallowing difficulties [22], [26], [31], [32], [35], [36]. While the focus of most studies was on the assessing performance of different classification methods based on computed features, few studies have directly compared extracted features in two directions of A-P and S-I to find out about the dissimilarities between the swallowing vibrations in different anatomical directions [22], [36]–[38].…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by the above, we propose a novel algorithm for combining several classifiers based on their individual reputations, numerical weights that reflect each classifier's past performance. The algorithm is detailed in the next section and again is adapted from Nikjoo et al (2011).…”
Section: Majority Voting Algorithmmentioning
confidence: 99%
“…The advantage of the reputation-based algorithm over the majority voting algorithm lies in the fact that the former has a higher probability of correct consensus and a faster rate of convergence to the peak probability of correct classification (Nikjoo et al, 2011).…”
Section: Reputation-based Voting Algorithmmentioning
confidence: 99%
See 1 more Smart Citation